Accommodation or Extraction? Employers, the State, and the Joint Production of Active Labor Market Policy. (December 2018) - Cronert, Axel
Conventional wisdom among comparative political economists maintains that the participation of employers in policymaking and policy implementation, fostered by corporatist arrangements, is crucial to the successful expansion of active labor market policy (ALMP). This article introduces a transaction-oriented theory of corporatism, partisanship, and ALMP that challenges the dominant view. It argues that corporatist arrangements do not affect the overall scope of ALMP but facilitate particular types of ALMP programs, ones that require the joint participation of employers and the state and involve a transfer of public resources to employers. Corporatist arrangements facilitating such programs—which center-right parties tend to prefer over those produced unilaterally by the state—also shift the focus of partisan conflict over ALMP from the level of public expenditure to the structure. Evidence for these claims is provided by time-series cross-sectional analyses of twenty-one OECD countries since the mid-1980s.